Implementasi Video Pembelajaran terhadap Kemampuan Pemecahan Masalah Matematis Mahasiswa dalam Pembelajaran Daring Kalkulus Integral - Kurnia Putri Sepdikasari Dirgantoro; Robert Harry Soesanto; R. H. Yanti Silitonga (Universitas Bhinneka PGRI, 2021)
Mathematical problem-solving abilities need to be owned by prospective mathematics teachers so that they can teach it to their students later. Integral Calculus course is a course that students need to understand the next course, as well as a course that is closely related to school mathematics. This study aims to look at the significance difference in students problem-solving ability related to video learning implementation. The research design used was a nonequivalent control group design with the subject of 71 mathematics education students from two universities in Indonesia. The instrument used was a calculus prior knowledge test and mathematical problem-solving test, each of which consisted of 3 questions. Based on the statistical test, it was found that the mathematical problem-solving abilities of the two research groups differed significantly. The subject group who used the instructional video had better problem-solving abilities than the subject group whose learning used virtual face-to-face